Oral Presentations Abstracts: MODIFYING NATURAL BEHAVIORAL RESPONSES BY ENFORCING ETHICAL VALUES - DURAN, Jaume (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 According to different theories about neuroscience and ethics, we want to introduce the idea that the ethical values are very good levers to conduct human responses to their perceptions. These theories are based on very currently data about science and the central nervous system explained recently by a very important neuroscientist. In a very basic nervous system, the reptilian brain, humans can solve their fundamental interest and necessities, such as survival, breading, community behavior… In a more complex and posterior temporary nervous system, thanks to the known limbic brain, humans have been able to solve and to respond to their emotional problems, creating the memory center of our emotions. After this second moment and as a result of the global anthropological evolution, the cortical brain allows us to think, to deploy the global intelligences and take human decisions. Thanks to these three brain levels and their neurobiological connections, humans have developed other intangible brains, able to experience the ethics, the esthetics, and the spirituality. Our brain works as a whole. We are the result made up of more than 100.000 million connected neurons that form the brains. In some aspects, our four dimensions, the physical, the emotional, the rational and the transcendental faces act together, hand in hand. Our more ponderous decisions aren’t always rational; more than 80% of them are basically emotional. So, our spiritual manners can be showed by biophysically manifestations; conscientious and unconscientious affects us equally. Human brain is genetically prepared to answer. Historically formed to respond, the central nervous system can be explained as the most complex organ to produce responses to multiple previous perceptions. These perceptions can be tangible or not, external or internal, consciences or not, actual or memorized. Our point of view is that we can introduce ethical values as a non-conscientious response. Working from rational and emotional ways our ethical values, we will introduce them in our transcendental brain. All posterior relationship between the brain areas will influence the behavior response to the real perceptions that we are exposed to. So, to summarize, enforced ethical values can unconscientiously modify our behavioral response.